Spectator demand for the sport of kings. Issue 51 (2nd November 2021) - Buraimo, Babatunde; Coster, Neil; Forrest, David
ABSTRACT: We estimate a model capturing influences on attendance in British horseracing. A fixed effects regression is employed in analysing data containing information on attendances at 23, 999 race-days (2001–2018). The patterns of demand are similar to those found for other sports, for example, attendance is higher at weekends and in warmer months and is sensitive to the quality of the racing. Further, attendance falls when races have to compete with some televised sport of national significance. Controlling for a large number of characteristics, the pattern of results on year dummies implies considerable decline in public interest in attending race-days over the period. The pronounced negative trend in attendance suggests a need for modernizing the sport including attention to animal welfare issues, which might partly account for apparently growing public disillusion.